Structural Analyses and Assessment of Historical Çardak Caravanserai in Denizli - Şahin, Esra; Hamamcıoğlu Turan, Mine; Aktaş, Engin (Izmir Institute of Technology, 2019)
The assessment of historical masonry structures are significant in terms of transferring our cultural heritage to future generations. The conservation of these masonry structures is possible through investigating problems and their causes with tools such as structural modeling and analyses. In this study, the structural modeling and analyses of a historical masonry structure was aimed. Çardak caravanserai in Denizli was chosen as the case study since it has preserved its authenticity and integrity. In this scope, the software used for modeling and structural analyses was SAP2000 v20.2 commercial finite element software. For modeling, frame elements were used in the columns and shell elements were used in the other structural elements. Selfweight analysis, modal analysis and response spectrum analysis were conducted in terms of the assessment. The self-weight analysis was made under dead load. The analysis indicated the current state of the structure. In modal analysis, free vibration periods, mode shapes and mass participation ratios of the structure were determined. In response spectrum analysis, according to Turkish Siesmic Design Code 2018, mode integration method was used as linear calculation method. In this analysis, the khan was evaluated under the dead load and earthquake loads in the x and y directions. The structural elements that exceed the compressive, tensile and shear strength were identified as hot spots and recommendations on the further investigations on these critical points of the structure were presented.

Tarihi yığma yapıların değerlendirilmesi kültürel mirasımızın gelecek nesillere aktarılması açısından önem taşır. Bu yığma yapıların korunması ise yapıda mevcut problemlerin ve sebeplerinin yapısal modelleme ve analizler gibi araçlarla irdelenmesi ile mümkün olmaktadır. Bu çalışmada, bir tarihi yığma yapının modellenmesi ve analizleri hedeflenmiştir. Özgünlüğünü ve bütünselliğini korumuş olan; Denizli’de bulunan, Çardak kervansarayı örnek yapı olarak seçilmiştir. Bu kapsamda, modelleme ve yapısal analizler için kullanılan yazılım SAP2000 v20.2 ticari sonlu elemanlar analiz ve tasarım yazılımıdır. Modelleme için kolonlarda çubuk elemanlar, diğer yapı elemanlarında ise kabuk elemanlar kullanılmıştır. Değerlendirme için kendi ağırlığı altında analiz, modal analiz ve davranış spektrumu analizi yapılmıştır. Kendi ağırlığı altında analiz ölü yük altında yapılmıştır. Bu analiz yapının mevcut durumunu göstermiştir. Modal analizde, yapının serbest titreşim periyotları, mod şekilleri ve kütle katılım oranları belirlenmiştir. Davranış spektrumu analizinde, Deprem Yönetmeliği 2018’e göre, doğrusal hesaplama yöntemi olarak mod birleştirme yöntemi kullanılmıştır. Çardak han ölü yük ve x ve y yönündeki deprem yükleri altında değerlendirilmiştir. Basınç, çekme ve kayma gerilmelerini aşan yapı elemanları bölgeleri kritik noktalar olarak gösterilmiştir ve bu noktalar ile ilgili daha detaylı irdeleme yapabilmek için öneriler sunulmuştur.
Denizli'de Bulunan Tarihi Çardak Kervansarayının Yapı Analizi ve Değerlendirilmesi
Thesis (Master)--Izmir Institute of Technology, Civil Engineering, Izmir, 2019
Includes bibliographical references (leaves: 98-104)
Text in English; Abstract: Turkish and English
Keywords: Çardak Caravanserai; Denizli; Cultural heritage; Historical masonry structures